Facile synthesis of porous PdCu nanoboxes for efficient chromium(vi) reduction. Issue 24 (7th June 2019) - Qiao, Bin; Zhu, Jingyi; Liu, Yanping; Chen, Yu; Fu, Gengtao; Chen, Pei
Abstract : Porous PdCu nanoboxes were synthesized in a facile manner through a Cu2 O template-assisted strategy, exhibiting catalytic activity and reusability for hexavalent chromium (Cr(vi )) reduction. Abstract : Hollow porous nanostructures offer a multitude of advantages for heterogeneous catalysts over solid nanoparticle catalysts. Herein, we reported the facile synthesis of PdCu nanoboxes with porous shells through a Cu2 O template-assisted strategy, enabling efficient chromium-VI (Cr(vi )) reduction. The synthesis procedure involved the formation of well-defined Cu2 O nanocubes and the transformation of partial Cu2 O into a PdCu shell by a galvanic reaction. The structure/composition and formation mechanism of the PdCu nanoboxes were investigated in detail. When used as a heterogeneous catalyst, in the presence of formic acid (HCOOH), the PdCu nanobox demonstrated an excellent catalytic effect for Cr(vi ) reduction with low activation energy (Ea = 47.8 kJ mol −1 ) and a high kinetic constant ( k = 0.274 min −1 ). Moreover, the PdCu nanoboxes were recycled ten times without significant reduction in the transformation efficiency. The improved catalysis originated from the unique structure-/composition-dependent merits of the porous PdCu nanoboxes, which effectively promoted the dehydrogenation decomposition of HCOOH molecules.